Catulo,Virgilio, Horacio y Ovidio en la evocación modernista del poeta Manuel Reina - Cristóbal, Vicente (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
Manuel Reina (Puente Genil, 1856-1905) wrote poems about the figures of Catullus, Virgil, Horace and Ovid. These poems blend, with a modernist mentality and style, a great amount of information from literary historiography –which was a dominating tendency in his era– and scarce echoes of the reading of such poets.